Keanekaragaman Jenis Plankton pada Akar dan Perairan Sekitar Mangrove Desa Lembar Selatan, Kabupaten Lombok Barat - Ibadur Rahman; Chandrika Eka Larasati; Ayu Adhita Damayanti (Jurnal Ilmu Kelautan Lesser Sunda, 2021)
The mangrove ecosystem is one of the ecosystems in the estuary area that is unique and very sensitive to environmental changes. The large number of aquaculture businesses around Cemare Hamlet, West Lombok Regency have resulted in many mangrove areas being converted into pond cultivation locations. This will have an impact on the life of mangrove ecosystems such as plankton. This study aims to determine the abundance of plankton species around the mangrove area of ??Dusun Cemare, Sheet Selatan Village, West Lombok Regency. The research was conducted in May-October 2019 using a purposive sampling method by determining 7 stations to represent water conditions. Plankton analysis using the Lackey drop microtranscting method. The results showed that the mangrove ecosystem in Dusun Cemare was composed of 4 types, namely: Rhizophora sp., Avicenia sp., Bruguiera sp., And Soneratia sp. The plankton community in mangrove waters is composed of 13 types, while the abundance of plankton species (periphyton) attached to the mangrove roots consists of 6 types. The composition of plankton species which tends to be high indicates that the mangrove waters of Dusun Cemare are still feasible to sustain the survival of the associated biota in it.